2020
DOI: 10.3390/ijms21020544
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor A and VEGFR-1 Change during Preimplantation in Heifers

Abstract: Vascular endothelial growth factor A (VEGFA) plays a critical angiogenic role in the endometrium of placentalia during preimplantation. The role of VEGFA and its receptors is not fully characterised in bovine reproduction. We analysed the mRNA expression of VEGFA isoforms 121, 165 and 189, and VEGF receptors 1 and 2 in three experimental settings (A, B and C). We compared intercaruncular endometrium of cyclic to pregnant heifers at Days 12, 15 and 18 post insemination (Day 0), and between Day 15 and Day 18 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Quantitative real-time PCR (qPCR) was carried out using the KAPA SYBR FAST qPCR Kit (Kapa Biosystems, Wilmington, USA) on a CFX384 Real-Time PCR Detection System (Bio-Rad, Munich, Germany). The relative expression level (ΔCq) of each gene was generated by scaling the target gene Cq of each individual sample to the geometric mean of the Cq of three reference genes [H3 histone family member 3A (H3F3A), tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein zeta ( YWHAZ ) and beta-actin ( ACTB )] as described previously by Chiumia et al [ 35 ]. To calculate ΔΔCq to visualize the RNA expression pattern, ΔCq values of PEEC-G or ALI-PEEC-G were subtracted from ΔCq values of PEEC-L or ALI-PEEC-L, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative real-time PCR (qPCR) was carried out using the KAPA SYBR FAST qPCR Kit (Kapa Biosystems, Wilmington, USA) on a CFX384 Real-Time PCR Detection System (Bio-Rad, Munich, Germany). The relative expression level (ΔCq) of each gene was generated by scaling the target gene Cq of each individual sample to the geometric mean of the Cq of three reference genes [H3 histone family member 3A (H3F3A), tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein zeta ( YWHAZ ) and beta-actin ( ACTB )] as described previously by Chiumia et al [ 35 ]. To calculate ΔΔCq to visualize the RNA expression pattern, ΔCq values of PEEC-G or ALI-PEEC-G were subtracted from ΔCq values of PEEC-L or ALI-PEEC-L, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Media compositions applied for cell culture purposes are listed in Table 1. Phenol red-free DMEM/ Hams F12 1:1 (21,041,025), Ham's F12 (11,765,054), GlutaMAX (35,050,087), and Nu-serum growth medium supplement (11,563,600) were obtained from ThermoFisher Scientific, Waltham, USA. FBS (S0115, Lot 0742C), penicillin/streptomycin (A2212), amphotericin B (A2612), HEPES (L1613), and PBS (L1825), were purchased from Biochrom AG, Berlin, Germany.…”
Section: Media and Reagentsmentioning
confidence: 99%
“…For example, VEGF expression has been related to fetal weight increase in porcine embryos [ 55 ], in which VEGF expression was detected in TE cells at Day 14 of pregnancy [ 50 ]. VEGF , VEGFR-1 , and VEGFR-2 mRNA have been found in vitellin sacs and TEs of bovine embryos [ 49 , 56 , 57 ]. In humans, VEGF expression increases in the late luteal phase, while in bovine corpus luteum, VEGF mRNA is upregulated in the early luteal phase, and then is progressively downregulated until its levels increase again during pregnancy [ 58 , 59 ].…”
Section: Growth Factors and Early Developmentmentioning
confidence: 99%
“…Studies in bovine showed that the endometrium responds differently to cloned embryos as compared to embryos produced by in vitro fertilization (IVF), indicating abnormalities in embryo-maternal communication and pregnancy recognition signaling [ 77 , 78 ]. Subsequent studies revealed dysregulation of genes involved in cell signaling and placental development [ 79 , 80 ].…”
Section: Epigenetic Abnormalities In Embryos Fetuses and Offsprinmentioning
confidence: 99%